2013
DOI: 10.1002/14651858.cd004439.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for treating chronic osteomyelitis in adults

Abstract: Limited and low quality evidence suggests that the route of antibiotic administration (oral versus parenteral) does not affect the rate of disease remission if the bacteria are susceptible to the antibiotic used. However, this and the lack of statistically significant differences in adverse effects need confirmation. No or insufficient evidence exists for other aspects of antibiotic therapy for chronic osteomyelitis.The majority of the included trials were conducted over 20 years ago and currently we are faced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
180
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(191 citation statements)
references
References 64 publications
3
180
0
8
Order By: Relevance
“…No signifi cant diff erence was found in the incidence of adverse events for each administration route. 2 While the authors found no diff erences in their outcome measures, they felt there was insuffi cient evidence to draw any conclusions from what were outdated studies with small numbers and at moderate to high risk of bias. Clearly, antibiotic therapy has a role to play in the control of chronic infection but we still do not have the answers for optimal administration route or duration.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…No signifi cant diff erence was found in the incidence of adverse events for each administration route. 2 While the authors found no diff erences in their outcome measures, they felt there was insuffi cient evidence to draw any conclusions from what were outdated studies with small numbers and at moderate to high risk of bias. Clearly, antibiotic therapy has a role to play in the control of chronic infection but we still do not have the answers for optimal administration route or duration.…”
mentioning
confidence: 94%
“…This review focuses in particular on the choice of antimicrobial, the optimal route of administration and duration of therapy. 2 The authors performed the usual extensive Cochrane literature review but were able to include only eight small studies in total, of which only four were appropriate for inclusion in the meta-analysis. The included trials evaluated fi ve diff erent antibiotic comparisons (oral versus parenteral, parenteral then oral versus oral only, parenteral then oral versus parenteral only, oral versus another oral, parenteral versus another parenteral).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of bone infections in patients with fractures can involve operative débridement of necrotic bone followed by several weeks of systemic antibiotics, temporary fixation, and/or implantation of devices to promote bone regeneration [11,44]. For orthopaedic infections, Staphylococcus aureus is the most commonly isolated agent, accounting for more than 1 . 2 of all infections [28].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial biofilms are a protected mode of growth characterized by a high tolerance to the activity of antimicrobials compared with planktonic bacteria, which is partly attributable to the limited permeability of antimicrobials through the extracellular matrix surrounding the bacteria and the reduced metabolic state of the persister cells in the biofilm [11,28,44,50]. Although clinical studies have underscored the relationship between infection and nonunion of diaphyseal fractures [24], periarticular fractures also have high rates of infections complications.…”
Section: Introductionmentioning
confidence: 99%